2022
DOI: 10.3390/biom12101429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Renin-Angiotensin System on the Pathogeny and Pharmacotherapeutics of Neurodegenerative Diseases

Abstract: Brain neurodegenerative diseases (BND) are debilitating conditions that are especially characteristic of a certain period of life and considered major threats to human health. Current treatments are limited, meaning that there is a challenge in developing new options that can efficiently tackle the different components and pathophysiological processes of these conditions. The renin-angiotensin-aldosterone system (RAS) is an endocrine axis with important peripheral physiological functions such as blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 232 publications
0
6
0
1
Order By: Relevance
“…62,63 Moreover, over-activity of RAS is correlated with disease severity in different neurodegenerative disorders, including dementia, multiple sclerosis, amyotrophic lateral sclerosis, Huntington's disease, stroke, and traumatic brain injury. 64,65 Furthermore, dysregulation of brain RAS is also implicated in different mental and psychiatric disorders, such as bipolar disorder. 66 Bipolar disorder, previously known as manic depression, is a mental disorder characterized by periods of depression and periods of abnormally elevated mood that each last from days to weeks.…”
Section: B R Ain R a Smentioning
confidence: 99%
See 2 more Smart Citations
“…62,63 Moreover, over-activity of RAS is correlated with disease severity in different neurodegenerative disorders, including dementia, multiple sclerosis, amyotrophic lateral sclerosis, Huntington's disease, stroke, and traumatic brain injury. 64,65 Furthermore, dysregulation of brain RAS is also implicated in different mental and psychiatric disorders, such as bipolar disorder. 66 Bipolar disorder, previously known as manic depression, is a mental disorder characterized by periods of depression and periods of abnormally elevated mood that each last from days to weeks.…”
Section: B R Ain R a Smentioning
confidence: 99%
“…Similarly, ACEIs and ARBs are effective against Alzheimer's disease (AD) neuropathology by inhibiting inflammation and oxidative stress‐induced neuronal injury 62,63 . Moreover, over‐activity of RAS is correlated with disease severity in different neurodegenerative disorders, including dementia, multiple sclerosis, amyotrophic lateral sclerosis, Huntington's disease, stroke, and traumatic brain injury 64,65 …”
Section: Brain Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that exaggerated of brain RAS is linked with the development and progression of different neurodegenerative diseases such as Alzheimer diseases (AD), amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS) and other neurological disorders including traumatic brain injury and stroke. 49 …”
Section: Role Of Brain Ras In Neurodegenerative Di...mentioning
confidence: 99%
“…To combat cardiovascular pathologies (e.g., atherosclerosis, coronary artery disease and hypertension), important pharmaceuticals have been developed which either inhibit its synthesis (i.e., angiotensin-converting enzyme inhibitors) or block its receptor (i.e., AngII receptor blockers (ARBs)) [ 26 ]. Additionally, AngII acts on T cell receptors [ 51 ], modulating the immune and inflammatory responses that result in autoimmune diseases (e.g., rheumatoid arthritis, systemic lupus erythematosus and multiple sclerosis) [ 52 ], diseases arising from chronic hyper-inflammation (e.g., atherosclerosis, coronary artery disease and chronic kidney disease) [ 53 , 54 ] and neurodegenerative disorders (e.g., Alzheimer’s disease, multiple sclerosis and motor neuron disease) [ 55 , 56 ]. More recently, sartans (non-peptide ARBs) have proven effective in combating COVID-19, not only by inhibiting the infective process [ 57 ] but also by blocking AngII-mediated inflammatory responses (i.e., cytokine storm) [ 58 ].…”
Section: Introductionmentioning
confidence: 99%